2015
DOI: 10.1007/s00442-015-3293-7
|View full text |Cite
|
Sign up to set email alerts
|

Detecting mismatches of bird migration stopover and tree phenology in response to changing climate

Abstract: Migratory birds exploit seasonal variation in resources across latitudes, timing migration to coincide with the phenology of food at stopover sites. Differential responses to climate in phenology across trophic levels can result in phenological mismatch; however, detecting mismatch is sensitive to methodology. We examined patterns of migrant abundance and tree flowering, phenological mismatch, and the influence of climate during spring migration from 2009 to 2011 across five habitat types of the Madrean Sky Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…The onset of spring plant growth, or 'spring onset,' has shifted earlier in the year in recent decades amid rising global temperatures (Cleland et al 2007, Ault et al 2011, McCabe et al 2012. Whereas a longer growing season may increase carbon uptake and potentially mitigate climate change (Black et al 2000, Dragoni et al 2011, earlier leaf and flower emergence has led to phenological mismatches between plant resources and many of those animals depending upon them (Walther et al 2002, Schweiger et al 2008, Saino et al 2011, Burkle et al 2013, Kellermann and van Riper IIIrd 2015. Earlier spring onset can also lead to increased risk of false springs, when subsequent hard freezes damage new, vulnerable plant growth in ecological and agricultural systems (Cannell and Smith 1986, Inouye 2008, Knudson 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of spring plant growth, or 'spring onset,' has shifted earlier in the year in recent decades amid rising global temperatures (Cleland et al 2007, Ault et al 2011, McCabe et al 2012. Whereas a longer growing season may increase carbon uptake and potentially mitigate climate change (Black et al 2000, Dragoni et al 2011, earlier leaf and flower emergence has led to phenological mismatches between plant resources and many of those animals depending upon them (Walther et al 2002, Schweiger et al 2008, Saino et al 2011, Burkle et al 2013, Kellermann and van Riper IIIrd 2015. Earlier spring onset can also lead to increased risk of false springs, when subsequent hard freezes damage new, vulnerable plant growth in ecological and agricultural systems (Cannell and Smith 1986, Inouye 2008, Knudson 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Mean temperatures and the frequency of extreme weather events are predicted to continue increasing [2,3], likely reducing the mean performance of species [4,5]. Such global trends will interact with regional factors, such as spatial variation in climatic patterns or the timing of low tides [6,7], in sometimes complex and nonlinear ways [8]. In addition, evolutionary responses to environmental change can act over short time scales once thought to be the exclusive realm of ecological interactions and/or phenotypic plasticity [9,10], with important implications for species' abilities to resist and adapt to global change.…”
Section: Introductionmentioning
confidence: 99%
“…Our first objective was to determine patterns of coincidence in arrival and foraging behavior of three migratory wood-warbler species (Parulidae) with that of tree phenology. Although studies in other systems of North America have identified important tree phenophases that overlap with migratory bird stopover (e.g., Rodewald and Brittingham 2007, McGrath et al 2008, Strode 2009, Kellermann and van Riper III 2015, Wood and Pidgeon 2015, these relationships remain unclear in the oak savanna system of this study. Our second objective was to quantify the effect of the extreme difference in spring temperature on potential ecosystem regulating services that migratory birds provide.…”
Section: Introductionmentioning
confidence: 86%